The correlates of social phobia in OCD: Findings from a large clinical sample. (18th April 2021) - Tibi, Lee; Asher, Sapir; van Oppen, Patricia; van Balkom, Anton J. L. M.; Eikelenboom, Merijn; Visser, Henny A.; Penninx, Brenda W.; Anholt, Gideon E.
Abstract : Objectives: Obsessive‐compulsive disorder (OCD) is a debilitating psychiatric disorder, often complicated with comorbidities. Social phobia (SP) is the most frequent co‐occurring anxiety disorder in OCD, associated with increased clinical severity. However, no study had examined the relevance of interpersonal processes in this comorbidity, which are at the core of SP. This study characterized the clinical (i.e., symptom profile, age of onset, chronicity, and comorbidity), vulnerability (i.e., childhood trauma, negative life events), and interpersonal (attachment style, expressed emotion, and social support) correlates of comorbid SP in a large sample of OCD patients. Methods: We analysed the data of 382 OCD patients participating in the Netherlands Obsessive Compulsive Disorder Association (NOCDA) study. We examined the correlates of SP in OCD using self‐report questionnaires and structured clinical interviews. In addition, data of 312 non‐OCD SP patients were drawn from the Netherlands Study of Depression and Anxiety (NESDA), to compare the age of onset of SP between groups. Descriptive univariate analyses were followed by backward stepwise logistic regression analyses. Results: Social phobia was present among approximately 20% of OCD patients. Social phobia in OCD was associated with increased depression severity and decreased ratings of secure attachment style. Among OCD patients, SP had a significantly earlier age onset as compared to SP in non‐OCD patients. Conclusion: Social phobia in OCD might render a vulnerable clinical picture, characterized with early onset of SP symptoms, insecure attachment style, and increased depressive symptoms. Future studies should use prospective designs to better understand the nature of comorbid SP in OCD. Practitioner points: Approximately one fifth of OCD patients were diagnosed with comorbid social phobia in a large representative clinical sample. OCD patients with comorbid social phobia presented with a vulnerable clinical picture, characterized with increased depression severity and decreased ratings of secure attachment style. Social phobia in OCD was associated with an earlier AOO as compared to the AOO of social phobia without OCD. The findings are limited by a cross‐sectional design; thus, causality could not be assessed. Research is needed to further examine the mechanisms of comorbid social phobia in OCD.